Model of affective assessment of primary school students - Amir Syamsudin; Budiyono Budiyono; Sutrisno Sutrisno (REID (Research and Evaluation in Education), 2016)
This study aims to develop an instrument of affective assessment to measure the social competence of elementary school students in the learning process in schools. This study used the development model of Borg Gall’s approach which was modified into five phases, including the need analyses, developing draft of the product conducted by experts, developing an affective assessment instrument, trying out the affective assessment instrument conducted by teachers of primary education in Yogyakarta, and the dissemination and implementation of the developed affective assessment instrument. The subjects were elementary school students whose school implemented Curriculum 2013 in the academic year of 2013/2014. The validity and reliability of each construct of the affective instrument were established using the PLS SEM Wrap PLS 3.0 analysis program. The study finds the following results. First, the construct of Honesty, Discipline, Responsibility, Decency, Care, and Self-Confidence in the limited, main, and extended testing has been supported by empirical data. Second, the validity of Honesty, Discipline, Responsibility, Decency, Care, and Self-Confidence in the limited, main, and extended testing meets the criteria above 0.70 for each indicator of the loading factor and the criteria below 0.50 for each indicator score of the cross-loading factor. Third, the reliability of Honesty, Discipline, Responsibility, Decency, Care, and Self-Confidence in limited, main, and extended testing meets the criteria above 0.70 for both composite reliability and Cronbach’s alpha scores. Fourth, the number of indicators at preresearch was 53, and 10 indicators were rejected in the limited testing, and four indicators were rejected in the main testing, and one indicator was rejected in the extended testing.